PERINTAH UNTUK SALING MENGASIHI (YOHANES 15:9-17) - Damianus Batlayeri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2025)
This article examines the command to love one another in John 15:9-17 as the core of Johannine theology. The study is grounded in the distinctive features of John’s Gospel, where love is not understood merely as an ethical mandate but as participation in the Trinitarian love that flows from the Father to the Son and is extended to the disciples. Using literary, historical, linguistic, and theological approaches, this research analyzes the narrative structure, the historical context of the Johannine community, the meaning of key Greek terms (agapē, doulos, philos), and the history of interpretation from the Patristic era to modern theology. The findings reveal that love in John is ontological, forming the identity of the disciples, marking the authentic Christian community, and empowering the Church’s mission. The shift from servants to friends highlights the disciples’ participation in God’s salvific plan. This study contributes to a deeper understanding of Johannine theology of love and its relevance for contemporary Christian spirituality and ecclesial practice.